Overexpression of the regulatory subunit of glutamate‐cysteine ligase enhances monoclonal antibody production in CHO cells. Issue 8 (8th May 2017) - Orellana, Camila A.; Marcellin, Esteban; Gray, Peter P.; Nielsen, Lars K.
ABSTRACT: For decades, Chinese hamster ovary (CHO) cells have been the preferred host for therapeutic monoclonal antibody (mAb) production; however, increasing mAb titer by rational engineering remains a challenge. Our previous proteomic analysis in CHO cells suggested that a higher content of glutathione (GSH) might be related to higher productivity. GSH is an important antioxidant, cell detoxifier, and is required to ensure the formation of native disulfide bonds in proteins. To investigate the involvement of GSH in mAb production, we generated stable CHO cell lines overexpressing genes involved in the first step of GSH synthesis; namely the glutamate‐cysteine ligase catalytic subunit ( Gclc ) and the glutamate‐cysteine ligase modifier subunit ( Gclm ). The two genes were reconstructed from our RNA‐Seq de novo assembly and then were functionally annotated. Once the sequences of the genes were confirmed using proteogenomics, a transiently expressed mAb was introduced into cell lines overexpressing either Gclc or Gclm. The new cell lines were compared for mAb production to the parental cell line and changes at the proteome level were measured using SWATH. As per our previous proteomics observations, overexpressing Gclm improved productivity, titer, and the frequency of high producer clones by 70%. In contrast, overexpressing Gclc, which produced a higher amount of GSH, did not increase mAb production. We show that GSH cannot be linked to higher productivity and that Gclm may be controlling other cellular processes involved in mAb production yet to be elucidated. Biotechnol. Bioeng. 2017;114: 1825–1836. © 2017 Wiley Periodicals, Inc. Abstract : Glutamate‐cysteine ligase catalytic (Gclc) and regulatory (Gclm) subunits, involved in glutathione synthesis, were selected as targets for metabolic engineering to increase monoclonal antibody (mAb) productivity in CHO cells. The genes sequences were completed using RNA‐Seq de novo assembly followed by generation of stable CHO cell pools overexpressing either Gclc or Gclm. A mAb was then transiently expressed and compared to the parental cell line. Overexpressing Gclm improved mAb specific productivity, titer, and the frequency of high producer clones by 70%.